2004
DOI: 10.1002/col.20062
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐regional comparison of colour emotions Part I: Quantitative analysis

Abstract: Colour emotion is a feeling or emotion induced in our brains warm-cool, light-dark, deep-pale, heavy-light, vivid-sombre, gaudyplain, striking-subdued, dynamic-passive, distinct-vague, transparent-turbid, soft-hard, and strong-weak

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 9 publications
(5 reference statements)
6
90
0
Order By: Relevance
“…The methodologies used by Sato et al, 7 Xin and Cheng, 8 and Ou et al, [9][10][11] for deriving the emotion scale, as well as the results of the emotion scale models obtained, are the same or similar to those for the NCD. Hence, it can be said that the emotion scales proposed by Sato et al, Xin et al, 12,13 and Ou et al, also have the same defects in applications as those image scales of the NCD, previously described. For instance, any emotion scale in the color emotion models derived by Sato et al, Xin et al, and Ou et al, separately cannot have a good and simple relationship with the hue scale of the CIE L*a*b* color space because of the uncertainty and undefinability or complexity and incomprehensibility of these new emotion scales.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The methodologies used by Sato et al, 7 Xin and Cheng, 8 and Ou et al, [9][10][11] for deriving the emotion scale, as well as the results of the emotion scale models obtained, are the same or similar to those for the NCD. Hence, it can be said that the emotion scales proposed by Sato et al, Xin et al, 12,13 and Ou et al, also have the same defects in applications as those image scales of the NCD, previously described. For instance, any emotion scale in the color emotion models derived by Sato et al, Xin et al, and Ou et al, separately cannot have a good and simple relationship with the hue scale of the CIE L*a*b* color space because of the uncertainty and undefinability or complexity and incomprehensibility of these new emotion scales.…”
Section: Introductionmentioning
confidence: 84%
“…One hundred and sixty nine pairs of semantic differential words were acquired from the latest Chinese dictionary issued by the West-North Publication, and other related studies and writings. [7][8][9][10]12,[17][18][19][20][21][22][23][24][25][26][27][28] and used in this study. These pairs of words were further classified into 66 groups, and those in the same group had similar meanings.…”
Section: Wright and Rainwatermentioning
confidence: 99%
“…But this was not the case for warm -cool scale of colour emotion. Therefore, they extended their studies looking into the differences in lightness and chroma at 0 hue angle describing the differences between the three regions (Xin et al, 2004a;Xin, Cheng, Taylor, Sato & Hansuebsai, 2004b). Lee and Lee (2006) found that colour emotion was highly affected by its tone.…”
Section: Kaya and Eppsmentioning
confidence: 97%
“…Distinct-vague correlation was the least one. This might be account for the difference in meaning when translating causing different interpretation (Xin et al, 2004b) Ou et al (2010) conducted a cross-cultural comparison of colour emotion for two-colour combinations. Psychophysical experiments were conducted in the UK, Taiwan, France, Germany, Spain, Sweden, Argentina, and Iran to assess colour emotion for two-colour combinations using semantic scales warm/cool, heavy/ light, active/passive, and like/dislike.…”
Section: Cultural Impacts On Emotionsmentioning
confidence: 99%
“…In the last few years, though several articles have been proposed on the study of the psychological preference of people reflecting on products, including their colours, [3][4][5][6][7] aesthetics, [8][9][10][11][12][13] and shapes, 14 the effect of one's physiological characteristic on the evaluated psychological preference was seldom taken into consideration. To overcome this shortcoming, the element of physiological characteristic is considered in this study such that the result is helpful for applying to product design for customization and personalization.…”
Section: Introductionmentioning
confidence: 99%